ORAYLÍQ AZIYA REGIONÍNDA JER-SUW RESURSLARÍNAN PAYDALANÍWDÍŃ SOCIAL-EKONOMIKALÍQ MAShQALALARÍ - Nurlanov, A.S. (SCIENCE and SOCIETY, 2025)
The article reveals the socio-economic problems of using groundwater resources in the regions of Central Asia, including the socio-economic problems of using water resources in the Amudarya and Syrdarya river basins.
Keywords: Aral Sea; Amudarya; Syrdarya; Pamir; Tien Shan; climate; river; canal; water resources; agriculture; ecology